The concept of the institution of the rights of the child and its place in the modern legal system - Sharakhmetova Umida Shaakbarovna (Genius Journals, 2023)
Ensuring and protecting children's rights is a priority of state policy. The recognition of children's personal and property rights, their observance, protection and proper regulation of relations arising from them should be an important condition for the development of all spheres of social and economic life in our country. The article comprehensively analyzes the scientific and practical problems connected with the regulation of children's rights in the current legislation, the determination of directions of their solution is an important theoretical and practical task for the improvement of the relevant section of the civil and family legislation
Keywords: relationship of family legal; civil legal relations; minor parent